WATER QUALITY ANALYSIS OF MEDCHAL LAKE OF HYDERABAD, TELANGANA (CAHIERS MAGELLANES-NS, 2024)
The water is very essential component of Earth and the freshwater source is very less compared to marine water. The Medchal lake is a nature preserve located in Medchal, Telangana, India, previously it is called as Medichelama. As the urbanization is growing the lake size has been decreased and the water quality is depleting. The study has included water quality assessment of lake for three seasons and samples were collected at three locations. Sixteen physico-chemical parameters were chosen for analysis such as Temperature, PH, electronic conductivity, total dissolved solids, total hardness, total alkalinity, chloride, calcium, magnesium, nitrites, nitrates, ammonia, phosphate, phosphorus, dissolved oxygen. Finally, results of the analysis were compared with water quality standards such as BIS 10500 (1991). It is observed that most the parameters are above the desirable limit and dissolved oxygen is less when compared the desirable limits. The reasons may be pollution due to over exploitation, urbanization and industrialization. The decreased oxygen levels may be due to eutrophication. The study suggests the need for restoration of lakes so that the water can be consumable.